2008
DOI: 10.1007/s00213-008-1199-3
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus functions in rats of AM1346, a high-affinity CB1R selective anandamide analog

Abstract: Objective To characterize in vivo the high-affinity CB 1 cannabinoid receptor (CB 1 R) selective anandamide analog AM1346 [alkoxyacid amide of N-eicosa-tetraenylamine] using drug discrimination. Substitution tests involved Δ 9 -tetrahydrocannabinol (Δ 9 -THC) and R-(+)-methanandamide (mAEA), a metabolically stable analog of anandamide (AEA), as well as the CB 1 R antagonist/inverse agonist rimonabant; D-amphetamine and morphine were also examined to assess pharmacological specificity. Materials and methods Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
(51 reference statements)
2
14
1
Order By: Relevance
“…The above two ligands mostly substitute for each other’s discriminative stimulus effects (Järbe et al 1998, 2000). However, in earlier work, we also pointed out differences in their pharmacological effects (e.g., Järbe et al 2001, 2003a, b, 2009). Using the two different discriminations allows us to explore in more detail potential differences in CB 1 R activation which could be attributed to variations in ligand–receptor binding interaction(s) that may reflect differences in signaling mechanisms.…”
Section: Introductionmentioning
confidence: 53%
“…The above two ligands mostly substitute for each other’s discriminative stimulus effects (Järbe et al 1998, 2000). However, in earlier work, we also pointed out differences in their pharmacological effects (e.g., Järbe et al 2001, 2003a, b, 2009). Using the two different discriminations allows us to explore in more detail potential differences in CB 1 R activation which could be attributed to variations in ligand–receptor binding interaction(s) that may reflect differences in signaling mechanisms.…”
Section: Introductionmentioning
confidence: 53%
“…A variety of these analogs with good affinity for the CB 1 receptor have been shown to produce THC-like discriminative stimulus effects in several species (Järbe et al 2001; Stewart and McMahon 2011; Wiley et al 1997; Wiley et al 2004). Further, several of these analogs have been trained as discriminative stimuli, with substitution and cross-substitution with THC as the typically observed pattern (Järbe et al 2009; Järbe et al 2001; Wiley et al 2004; Wiley et al 2011). Consistent with these previous results, O-1812 fully and dose-dependently substituted for THC in both groups of mice, showing greater potency than anandamide in FAAH knockout mice and compared to THC in mice of both genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In rats and mice, treatment with the selective FAAH inhibitor URB597 or the non-selective serine hydrolase inhibitor PMSF potentiates the discriminative stimulus properties of AEA sufficiently to fully substitute for Δ9-THC (Solinas et al ., 2007; Vann et al ., 2009), though URB597 alone does not produce Δ9-THC appropriate responding (Gobbi et al ., 2005; Solinas et al ., 2007). Recent studies have also shown that Δ9-THC and (R)-methanandamide each fully generalize to the discriminative stimulus produced by the CB 1 -selective AEA analog AM1346 (Jarbe et al ., 2009) and Δ9-THC, WIN 55,212-2 and the selective CB 1 agonist AM678 fully generalize to the discriminative stimulus of (R)-methanandamide through a CB 1 receptor-sensitive mechanism (Jarbe et al ., 2010). The discriminative properties of (R)-methanandamide, AEA (following URB597 administration), WIN 55,212-2, AM678, AM1346 and Δ9-THC are each blocked by SR 141716A and are therefore thought to be CB 1 receptor dependent (Jarbe et al ., 2000; Jarbe et al ., 2001; Jarbe et al ., 2009; Jarbe et al ., 2010; Jarbe et al ., 1998; Solinas et al ., 2007).…”
Section: Behavioral Effects Produced By Endocannabinoidsmentioning
confidence: 99%
“…Recent studies have also shown that Δ9-THC and (R)-methanandamide each fully generalize to the discriminative stimulus produced by the CB 1 -selective AEA analog AM1346 (Jarbe et al ., 2009) and Δ9-THC, WIN 55,212-2 and the selective CB 1 agonist AM678 fully generalize to the discriminative stimulus of (R)-methanandamide through a CB 1 receptor-sensitive mechanism (Jarbe et al ., 2010). The discriminative properties of (R)-methanandamide, AEA (following URB597 administration), WIN 55,212-2, AM678, AM1346 and Δ9-THC are each blocked by SR 141716A and are therefore thought to be CB 1 receptor dependent (Jarbe et al ., 2000; Jarbe et al ., 2001; Jarbe et al ., 2009; Jarbe et al ., 2010; Jarbe et al ., 1998; Solinas et al ., 2007). These studies provide strong evidence of similar pharmacological effects produced by phytocannabinoids (e.g.…”
Section: Behavioral Effects Produced By Endocannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation